Measurement Tools of Pediatric Nutrition and Health Suitable or Adaptable for Low- and Middle-Income Countries in Field Research Settings - Kalami, Venus S.; Miller, Laurie C.; Ausman, Lynne; Rogers, Beatrice (International Journal of Child Health and Nutrition, 2022)
Background: Micronutrient status, body composition, gastrointestinal (GI) functioning, and neurological functioning are important facets of pediatric nutrition and health. When studied in low- and middle-income countries (LMIC), information about these elements is usually obtained via standardized surveys and traditional anthropometry. While convenient, these evaluations offer limited information that may be prone to error and bias. However, a variety of underutilized objective measurement tools exist which can promote a more objective, comprehensive, and deeper understanding of these aspects of pediatric nutrition and health in LMIC. Objective: Identify field-friendly, relatively low-cost, and portable tools that provide objective measurements of micronutrient status, body composition, GI functioning, and neurological functioning in young children. Methods: A narrative review of the literature was conducted to assess the state-of-the-art field-friendly research tools targeting micronutrient status, body composition, GI functioning, and neurological functioning in children in LMIC. Results: A number of field-friendly tools addressing the domains of micronutrient status, GI health, body composition, and neurological functioning were identified. While many tools remain to be fully validated, these tools have yet to be used to their full potential in field-based pediatric nutrition and health research in LMICs. Conclusions: More robust, field-friendly assessment methods will help to refine knowledge on the state of pediatric health of vulnerable children in LMIC. Such awareness could contribute to the design of interventions, programs and policies, and further research.